Geospatial As-built Drawing Management Techniques in Building Practice: A Framework for Facility Management in Nigerian Universities - Rasheed Busari; Jubril Jimoh; Amos Ayoola; Najeem ADERIBIGBE (International Journal of Research and Applied Technology (INJURATECH), 2026)
Geospatial as-built drawing management is increasingly vital in modern building practice as it enhances efficiency, performance, and facility lifecycle management. This study explores the deployment of a geospatial technology for managing as-built drawings within a Nigerian university campus. It assesses the current state of documentation, staffing capacity, and digital infrastructure required for effective implementation. Spatial data were collected using GPS and satellite imagery, processed in ArcGIS 10.8. Attribute data on buildings and staff were sourced from the university’s establishment and records office. Analyses included simple percentages and spatial hyperlinking in ArcGIS. Findings reveal that as-built drawings exist mainly in fragmented formats—paper archives and standalone digital files—with minimal geospatial referencing and limited integration into centralized systems. This fragmentation hinders efficient data retrieval, maintenance planning, and informed decision-making. Significant staffing gaps were identified, as most personnel are traditional built environment professionals lacking expertise in Geographic Information Systems (GIS), Building Information Modelling (BIM), and digital data management. Digital infrastructure deficiencies further constrain progress, including inadequate computing systems, absence of dedicated geospatial platforms, lack of centralized databases, and poor network connectivity. These limitations collectively hinder the transition to integrated geospatial as-built management. The study concludes that successful implementation requires accurate and standardized documentation, skilled interdisciplinary personnel, and robust digital infrastructure. It recommends strategic investment in training, technology, and system integration to achieve efficient geospatial as-built drawing management.